Documentação colaborativa de software através de anotações contextuais. - Nuno Miguel Leite Pereira de Sousa (2015)
Software documentation, despite still being considered secondary in relation to other artifacts that result from the development process, is fundamental in order to use and understand software in an efficient way. The software development process has been evolving over time, and is now an increasingly social activity, namely compared to other popular frameworks on the web. However, the same principles can be applied to small agile development teams. In this context, minimalist documentation, where only the bare minimum content is created, which will evolve according to the specific needs of the users, has been rising in popularity. The interaction and communication between both readers and authors, with the goal of debating what changes must be made to the documentation, is key to this evolution.The main goal of this work is to demonstrate that this communication can be the subject of improvement, namely with the use of contextual annotations in the documentation. In order to achieve this goal, a wiki has been developed, which will serve as platform for collaborative software documentation. Then, the possibility to add comments to a certain page and annotations to specific portions of that page was added to the wiki, thus creating a friendly environment to discussion between readers and authors.Finally, in order to verify that the developed tool fulfills its goal of improving communication and interaction between the various interveners, it will be tested in a small software development team.